PROFESSIONAL LEARNING OF PHYSICAL EDUCATION PROFESSORS: A LOOK AT LIFELONG PROFESSIONAL DEVELOPMENT - Fabrício João Milan; Gelcemar Oliveira Farias (Journal of Physical Education)
ABSTRACT The purpose of this research is to analyze theoretically the lifelong learning of Physical Education professors at university. During the biographical processes of life, the teacher goes through episodic experiences that unfold in skills, knowledge, among other elements. This process occurs by the meaning that is attributed to such experiences, meaning this constructed by levels of critical reflection that qualify the professional performance. In this scenario, it is important to emphasize and consider that this process is social, and the university professor is an individual socially interconnected to a social culture, which in turn reveals the idiosyncratic process of learning of this subject. Thus, in his biography, the life experiences of the university professor lead his professional development.